Prospects of the Agro-industrial Complex Development: Economic Diversification, Business Development, Mono-industry Town Strengthening and Expansion - Prokhorova, Victoria V.; Klochko, Elena N.; Kolomyts, Oksana N.; Gladilin, Alexandr V. (International Review of Management and Marketing, 2016)
Great dependence on competitiveness of one city-forming enterprise or several enterprises which conduct their activity within the uniform production and technological process, the lack of financial and other resources for solution of social and economic problems in an emergency present a defining feature of mono-industry towns. Exactly for this reason some mono-industry towns connected with enterprises of raw and investment complexes, and mechanical engineering were greatly influenced by consequences of the world economic crisis in 2015. The problem concerning mono-industry towns of Russia is among the most urgent complex with great social importance. Its solution based on the general principles for the whole group of mono-industry towns (economic diversification, small business development, inter-city and inter-municipal interrelation strengthening and expansion, and so on, at the same time has a special individual character for each population. For the purpose of mono-industry town economic diversification it is necessary to increase a share of small and medium enterprises of the agro-industrial complex. Activation of development of the transport, power and information infrastructure for effective exploitation of natural resources, coordinated and accelerated development of the whole district, realization of the transit potential and creation of the conditions for full and large-scale interaction of the economic region of east and western parts of the Russian Federation. Keywords: mono-industry town, agro-industrial complex, personal subsidiary farm, food security JEL Classifications: Q18, R11, R58